Intravenous thrombolysis is more effective in ischemic cardioembolic strokes than in non-cardioembolic? - Sofia Rocha; Arnaldo Pires; Joana Gomes; João Rocha; Filipa Sousa; João Pinho; Margarida Rodrigues; Carla Ferreira; Álvaro Machado; Ricardo Maré; João Ramalho Fontes (Arquivos de Neuro-Psiquiatria)
It was suggested that intravenous thrombolysis (IT) leads to larger extent recanalization in cardioembolic stroke. In this work we assess if this has beneficial clinical traduction. METHOD: We evaluated 177 patients undergoing IT, which were categorized into cardioembolic (CE) and non-cardioembolic (NCE). National Institutes of Health Stroke Scale (NIHSS) and modified Rankin scale were compared. RESULTS: The mean age was 67.4±12.01 and 53.8% were male. The mean NIHSS was: 14 (admission), 9 (24 h) and 6 (discharge), similar in subgroups. The difference between NIHSS at admission and 24 hours was 4.17±4.92 (CE: 4.08±4.71; NCE: 4.27±5.17, p=0.900) and at admission and discharge there was an average difference of 6.74±5.58 (CE: 6.97±5.68; NCE: 6.49±5.49, p=0.622). The mRS at discharge and 3 months was not significantly different by subtype, although individuals whose event was NCE are more independent at 3 months. CONCLUSION: Ours findings argue against a specific paper of IT in CE. It can result from heterogeneity of NCE group.